Self‐supported thin‐film electrode consisting of transition metal borides for highly efficient hydrogen evolution - Qi Miao; Lihong Bao; Yuxin Gao; Hao Wang; Yongjun Cao; Wei Li; Lei Li; Xiaowei Yang; Jijun Zhao; Ruguang Ma (Carbon Energy)
Abstract Transition metal borides (TMBs) are a new class of promising electrocatalysts for hydrogen generation by water splitting. However, the synthesis of robust all‐in‐one electrodes is challenging for practical applications. Herein, a facile solid‐state boronization strategy is reported to synthesize a series of self‐supported TMBs thin films (TMB‐TFs) with large area and high catalytic activity. Among them, MoB thin film (MoB‐TF) exhibits the highest activity toward electrocatalytic hydrogen evolution reaction (HER), displaying a low overpotential (η10 = 191 and 219 mV at 10 mA cm−2) and a small Tafel slope (60.25 and 61.91 mV dec−1) in 0.5 M H2SO4 and 1.0 M KOH, respectively. Moreover, it outperforms the commercial Pt/C at the high current density region, demonstrating potential applications in industrially electrochemical water splitting. Theoretical study reveals that both surfaces terminated by TM and B atoms can serve as the active sites and the H* binding strength of TMBs is correlated with the p band center of B atoms. This work provides a new pathway for the potential application of TMBs in large‐scale hydrogen production.